Entrepreneurial Spirit of Students: Innate or Acquired - El Alaoui Ismaili Moulay Youssef; Ibnrissoul Nafii; Abouljaouad Kamal (6th International OFEL Conference on Governance, Management and Entrepreneurship. New Business Models and Institutional Entrepreneurs: Leading Disruptive Change. April 13th - 14th, 2018, Dubrovnik, Croatia, 2018)
This paper questions the spirit of entrepreneurship among students in Morocco. It presents the results of a survey among students of FSJES and those of vocational training (BTS and ISTA) BTS equivalent to (Higher Technical Diploma), ISTA (Higher Institute of Applied Technology). The results show that few students are willing to start their own business, and that most students are not familiar with the professional field and have not had entrepreneurship courses and trainings at the university, so there is a lot of efforts to be made by governments and universities to promote entrepreneurship among students.
Keywords: 650; Entrepreneur; Entrepreneurial spirit; Professional training